2013
DOI: 10.1111/jtxs.12019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Structural Differences on Perceived Sweetness in Semisolid Dairy Matrices

Abstract: The objective of this work was to explore the possibility of obtaining dairy desserts of similar consistency and with different sweetness intensity. Eight formulations were prepared varying in the thickener type and concentration: carboxymethyl cellulose (1.1 and 1.3% w/w) and modified starch (3.5 and 4.0% w/w) and the milk type (whole or skimmed). The amounts of sugar (10% w/w), colorant (37.5 mg/kg) and lemon flavor (120 mg/kg) were fixed. Changes in composition and structure provide products with similar va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…4c, d). The good correlation obtained between the two index values (R 2 = 0.92) seems to confirm the practical utility of both of these instrumental measurements to predict perceived consistency or thickness in this type of semisolid product (Cook et al 2003;Arancibia et al 2013b).…”
Section: Microstructurementioning
confidence: 52%
See 1 more Smart Citation
“…4c, d). The good correlation obtained between the two index values (R 2 = 0.92) seems to confirm the practical utility of both of these instrumental measurements to predict perceived consistency or thickness in this type of semisolid product (Cook et al 2003;Arancibia et al 2013b).…”
Section: Microstructurementioning
confidence: 52%
“…However, some authors have found that oral thickness correlates with different rheological indices. It has been confirmed that one of them, apparent viscosity at a shear rate of 50 s −1 , suggested by Wood in 1968, has practical utility as a possible instrumental index of thickness perceived in semisolid foods (Cook et al 2003;Arancibia et al 2013b). Consequently, apparent viscosity values at a shear rate of 50 s −1 (η 50 ) were also calculated.…”
Section: Flow Propertiesmentioning
confidence: 81%
“…Pauloski et al (), also reported different effects of bolus volume in salty taste perception in patients treated for head and neck cancer, describing a saltier perception when bolus volume was higher. Other studies (Arancibia, Costell, & Bayarri, ; Spence, ), showed that in healthy people the salivary flow, which also is very variable among people, affects the gustatory, and flavor perception. Also this result could account for the differences between the present study and previous ones, since different assessors were used.…”
Section: Discussionmentioning
confidence: 93%
“…Also, adding food thickeners is believed to increase texture and decrease aroma and taste intensity, although these effects seem to be dependent on thickener type (Bayarri, Rivas, Izquierdo, & Costell, 2007;Guinard & Marty, 1995;Hollowood, Linforth, & Taylor, 2002). Differences in how thickener type and concentration affect perceived flavour, taste and texture in dairy systems can be explained not only by their contribution to product structure and rheology, but also by their influence on the product matrix transformation during oral processing (Arancibia, Costell, & Bayarri, 2013;Engelen & van der Bilt, 2008;Gierczynski, Guichard, & Laboure, 2011). Starch and carboxymethyl cellulose (CMC) are the most widely used thickeners in dairy desserts.…”
Section: Introductionmentioning
confidence: 99%